Detection and quantitation of synthetic cannabinoids in whole blood, urine and herbal products and its application to postmortem cases in Johannesburg, South Africa - Pon, Dale (My University, 2016)
A study was conducted by J.W. Huffman in 1994, to design new compounds with effects comparable to natural cannabinoids, for example THC. This resulted in the synthesis of JWH- 018, which, along with C8 analogs of the cannabinoid CP 47,497 became the most common synthetic additives in several herbal blends known as ‘Spice’. These herbal blends were originally sold online and in head shops (shops specialising in cannabis and tobacco paraphernalia) without age restriction or legal implications. In 2008 synthetic cannabinoids were identified in these mixtures and from early 2009, numerous countries began implementing legislation to monitor and control these drugs. The aim of this project was to develop and validate a LC-MS method for the detection and quantitation of several synthetic cannabinoids (JWH-018, JWH-019, JWH-073, JWH-081, JWH-122 JWH-200, JWH-250, AM-2201, (±)-CP 47,497, (C8)-CP 47,497, HU-211) and selected metabolites (JWH-018 N-(4-hydroxypentyl) metabolite and JWH-073 N-(3-hydroxybutyl) metabolite) in whole blood and urine. Further aims were to apply it to postmortem cases at the Johannesburg Forensic Pathology Services Medicolegal Laboratory (FPS-MLL) to assess the prevalence of these synthetic cannabinoids amongst the local postmortem population; as well as to known positive powder and urine samples obtained from a horseracing laboratory In Australia. Urine samples were extracted utilising an SPE method, while blood samples were extracted utilising an LLE method. LC-MS analysis was performed on a Thermo Fisher Q Exactive Orbitrap. Analytical parameters including: limit of detection (LOD), limit of quantitation (LOQ), stability, matrix effects, selectivity, linearity, repeatability, accuracy, and recovery were assessed for each analyte. None of the postmortem cases were found to contain any of the targeted analytes, although validated methods for urine and whole blood were developed based on existing routine screening methods. The sample population could be extended to living subjects such as those in drug rehabilitation centres or in hospitals to get a more accurate representation of the overall usage in South Africa.
A dissertation submitted to the Faculty of Health Science, University of the Witwatersrand, Johannesburg, in fulfillment of the requirements for the degree: MSc (Med) in forensic medicine aDepartment of Forensic Medicine and Pathology, School of Clinical Medicine, Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, South Africa & bThe Laboratory of The National Horseracing Authority of Southern Africa Johannesburg, 2016